Editorial - Editorial, Equipo (Avances en Supervisión Educativa, 2009)
The agreement called Bologna, more specifically the agreement on the construction of a European Higher Education Area, must mean an improvement, an advance in the university education of students that allows our graduates to compete professionally in an increasingly global world. Therefore, a better qualification of our students through degrees that qualify for a qualified job will allow us to harmonize our university education with our global environment.